Rescue of injured motoneurones by grafted neuroectodermal stem cells Effect of the location of graft - Pajenda Gholam (RESTORATIVE NEUROLOGY AND NEUROSCIENCE, 2013)
Purpose: Avulsion of one or more ventral roots from the spinal cord leads to the death of the majority of affected motoneurons. In this study we investigated whether immortalized clonal neuroectodermal stem cells applied to the injured cord in various ways impart neuroprotection on motoneurons otherwise destined to die. Methods: The lumbar 4 (L4) ventral root of Sprague-Dawley rats was avulsed and reimplanted ventrolaterally into the injured cord. Clonal neuroectodermal murine stem cells (NE-GFP-4C) were placed in fibrin clot around the reimplanted root, were injected immediately following avulsion into the reimplanted ventral root or directly into the L4 segment. Three months after the primary surgery the L4 motoneuron pool was retrogradely labelled with Fast blue and the numbers of reinnervating motoneurons were determined. Functional recovery was tested biweekly through the use of the CatWalk automated gait analysis system. Results: Transplantation of neuroectodermal stem cells into the reimplanted root or into the L4 spinal segment resulted in similarly extensive regeneration of the motoneurons (671 +/- 26 and 711 +/- 14 L4 motoneurons, respectively). In these groups significant functional recovery was achieved. The negative controls and animals with periradicular stem cell treatment showed poor motor recovery and reinnervation (42 +/- 10 and 65 +/- 2.5, respectively). Conclusion: This study provides evidence that neuroectodermal stem cell transplantation into the reimplanted ventral root induces as successful regeneration of injured motoneurons as stem cells grafted into the spinal cord.